Awake seizures after pure sleep-related epilepsy: a systematic review and implications for driving law. Issue 2 (9th February 2010) - Thomas, R H; King, W H; Johnston, J A; Smith, P E M
Abstract : Who with sleep seizures is safe to drive? Driving law is controversial; ineligibility varies between individual US states and EU countries. Current UK driving law is strongly influenced by a single-centre study from 1974 where most participants were not taking antiepileptic drugs (AEDs). However, pure sleep-related epilepsy is often fully controlled on medication, and its withdrawal can provoke awake seizures. This systematic review asked, 'What is the risk of awake seizures in pure sleep-related epilepsy?' 9885 titles were identified; 2312 were excluded (not human or adult); 40 full texts were reviewed; six papers met our inclusion criteria; each of these six studies had a different pure sleep-related epilepsy definition. Using the largest prospective study, we were able to calculate next year's awake seizure chance (treated with antiepileptic medication). This was maximal in the second year: 5.7% (95% CI 3.0 to 10.4%). European licensing bodies including the UK's Driver and Vehicle Licensing Agency broadly accept a risk of less than 20% for Group 1 licensing. However, this study excluded patients with frontal-lobe epilepsies. Furthermore, follow-up (n=160) varied from 2 to 6 years, yet new awake seizures may occur even after 10–20 years of pure sleep-related epilepsy A paucity of evidence underpins present licensing law; current rulings would be difficult to defend if legally challenged. The law may be penalising people with pure sleep-related epilepsy without increased risk of awake seizures, while failing to identify subgroups at unacceptable risk of an awake seizure at the wheel.